Determination of thermal comfort criteria of outdoor plaza - an outdoor field experiment on human subjects using PMV scale - Ibrahim, Md. Najib; Abdul Majid, Noor Hanita (1999)
Although PMV scale was designed for the indoor, it was used in the thermal comfort assessment of the outdoors because of its practicality. PMV values can be read directly from a portable integrated equipment, which require only one sensor. The original PMV scales were calibrated based on the perception of foreign human subjects under indoor laboratory condition. In this experiment, the original PMV scale was modified for outdoors local application based on perception of local human subjects in a plaza.